Decreased PGF may contribute to trophoblast dysfunction in fetal growth restriction. Issue 3 (September 2017) - Wu, Wei-Bin; Xu, Yue-Ying; Cheng, Wei-Wei; Yuan, Bo; Zhao, Jiu-Ru; Wang, Yan-Lin; Zhang, Hui-Juan
Abstract : Fetal growth restriction (FGR) threatens perinatal health and is correlated with increased incidence of fetal original adult diseases. Most cases of FGR were idiopathic, which were supposed to be associated with placental abnormality. Decreased circulating placental growth factor (PGF) was recognized as an indication of placental deficiency in FGR. In this study, the epigenetic regulation of PGF in FGR placentas and the involvement of PGF in modulation of trophoblast activity were investigated. The expression level of PGF in placental tissues was determined by RT-qPCR, immunohistochemistry and ELISA. DNA methylation profile of PGF gene was analyzed by bisulfite sequencing. Trophoblastic cell lines were treated with ZM-306416, an inhibitor of PGF receptor FLT1, to observe the effect of PGF/FLT1 signaling on cell proliferation and migration. We demonstrated that PGF was downregulated in placentas from FGR pregnancies compared with normal controls. The villous expression of PGF was positively correlated with placental and fetal weight. The CpG island inside PGF promoter was hypomethylated without obvious difference in both normal and FGR placentas. However, the higher DNA methylation at another CpG island downstream exon 7 of PGF was demonstrated in FGR placentas. Additionally, we found FLT1 was expressed in trophoblast cells. Inhibition of PGF/FLT1 signaling by a selective inhibitor impaired trophoblast proliferation and migration. In conclusion, our data suggested that the PGF expression was dysregulated, and disrupted PGF/FLT1 signaling in trophoblast might contribute to placenta dysfunction in FGR. Thus, our results support the significant role of PGF in the pathogenesis of FGR.